THE CORRELATION BETWEEN THE OPEN SPACE EXISTENCE AND BUILDING HEIGHT ON JAKARTA’S ROADS - Linggasani, Made Anggita Wahyudi (Journal of Architectural Research and Education, 2020)
Jakarta, the capital of Indonesia, is indirectly experiencing rapid development in building construction. As a result, day by day Jakarta is becoming crowded by buildings and eventually forced to negate the existence of open space in one site. This condition is also experienced in Jalan Jaksa (a tourism area) and Jalan Wahid Hasyim (at the end of Jalan Jaksa). Both of these roads seem lacking in considering the existence of local development regulations that should pay attention to the rules of the building border line (GSB) and the road border line (GSJ). To find out the truth, the research will be conducted through the method of observing the city face on both roads. The analytical method used is correspondence analysis using variable height of buildings and the existence of open space in each building. Based on the results of the analysis, it was found that there are still many buildings that not applying the rules of the building border line (GSB) and the road border line (GSJ). Especially for one-story buildings that tend not to have a yard (open space area) on the front as a form of implementing the GSB / GSJ rules. Meanwhile, multi-storey buildings (2-storey, 3-storey, etc.) here in general have a yard in the front. The existence of the yard is actually important to be provided as an open space, because it can accommodate human activities and needs, such as a parking area or an assembly point when a disaster occurs.